Cognitive Dissonance Behavior in Online Consumers (Demographic and Cross Cultural Approach) - Edy, Irwan Christanto (Research Collaboration Community (Rescollacom), 2025)
This study aims to understand cognitive dissonance behavior in online consumers in a demographic and cross-cultural context. The research variables included cognitive dissonance, visual content of the website, psychological (emotions, preferences, perceptions), demographics and cross-culture. This study uses a quantitative approach. Novelty is a research with a demographic and cross-cultural approach in Indonesia. Indonesia has demographic and cultural diversity. The sampling method is purposive sampling. The data collection technique used questionnaires. Data was obtained by 428 respondents. Data analysis with SEM-PLS (Structural Equation Modeling – Partial Least Squares). This research produced a model. The model's findings show that demographics and cross-cultural have a significant impact on cognitive dissonance behavior in online consumers. The implications of future research are that online marketing strategies need to consider demographic and cross-cultural factors of a country so that online marketing strategies can be more effective.The limitation of research is that research is carried out with a quantitative approach, in the future it can be carried out with a qualitative approach or a quantitative qualitative mix method.